2001
DOI: 10.1002/kin.1066
|View full text |Cite
|
Sign up to set email alerts
|

A new mechanism for initiation of free‐radical chain reactions during high‐temperature, homogeneous oxidation of unsaturated hydrocarbons: Ethylene, propyne, and allene

Abstract: The initiation of free radical chain reactions by singlet carbene biradicals is proposed for homogeneous oxidation of typical unsaturated hydrocarbons, including ethylene, allene, and propyne. The mechanism features the production of singlet vinylidene and methylvinylidene by 1,1-H 2 elimination and 1,2-H shift, respectively, from ethylene and propyne. The singlet biradicals then react with molecular oxygen to initiate a free-radical chain process. The analysis used quantum chemistry calculations and detailed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 31 publications
1
4
0
1
Order By: Relevance
“…When a C=C double-bond is present in the fuel molecule, H-atom addition reactions should also be considered [40]. The energy barrier for the H-atom addition to ethylene was reported to be 8 kcal/mol [49], which is below the energy barrier for the initial H-atom abstraction reaction induced by O 2 [50] and can thus happen already at lower temperatures. Therefore, H-atom addition is expected to proceed at lower heights above the burner where flame temperatures are relatively low and H-atoms are present through back-diffusion.…”
Section: Fuel Consumption Via H-atom Addition Reactionsmentioning
confidence: 99%
“…When a C=C double-bond is present in the fuel molecule, H-atom addition reactions should also be considered [40]. The energy barrier for the H-atom addition to ethylene was reported to be 8 kcal/mol [49], which is below the energy barrier for the initial H-atom abstraction reaction induced by O 2 [50] and can thus happen already at lower temperatures. Therefore, H-atom addition is expected to proceed at lower heights above the burner where flame temperatures are relatively low and H-atoms are present through back-diffusion.…”
Section: Fuel Consumption Via H-atom Addition Reactionsmentioning
confidence: 99%
“…Alternatively, a theoretical approach to acetylene oxidation in shock tubes suggested that vinylidene does play a critical primary role in these processes, which is contrary to Benson's view 85 of the irrelevance of vinylidene in C 2 H 2 chemistry. Singlet vinylidene also has been invoked as a primary reactant in the high-temperature oxidation of several unsaturated hydrocarbons, and a rate constant for its reaction with O 2 of 1.6 × 10 -11 cm 3 molecule -1 s -1 has been estimated. The reaction products are assumed to be two HCO radicals, which differs from the triplet vinylidene reaction with O 2 (see below).…”
Section: Vinylidene Radicals R2ccmentioning
confidence: 99%
“…Further, Another encouraging factor of the current results is the prediction of minor species such as aC3H4, pC3H4 and C2H2, which matched well with Aramco Mech 2.0 at 1100K. As explained in chapter 1, while C2H2 is one of the key soot precursors, aC3H4 and pC3H4 are also primary source of propargyl radicals, which is related to formation of benzene and PAH molecules [22], [83]. Thus, the results from the current study can be used to further improve these reaction models and help accurate prediction of soot precursors.…”
Section: Ethane Pyrolysis Results At Atmospheric Pressuresupporting
confidence: 69%